There will be a road - Jensen, Dwight William (Garden City, N.Y. : Doubleday, 1978)
In the late 1920's, two young men spend the winter in the Idaho mountains cutting trees for posts, living in a dugout, and ultimately fighting for their lives in a blizzard.
Keywords: Survival -- Fiction; Winter -- Fiction; Idaho -- Fiction